Agriculture Exposure and Time to Pregnancy Among Women Enrolled in the French Prospective Cohort AGRICAN. Issue 5 (May 2021) - Pons, Romain; Boulanger, Mathilde; Tual, Séverine; Busson, Amandine; Renier, Marine; Perrier, Stéphanie; Levêque-Morlais, Noémie; Marcotullio, Elisabeth; Baldi, Isabelle; Lebailly, Pierre
Abstract : Objectives: In few retrospective studies, prolonged time-to-pregnancy (TTP) was observed for women exposed to pesticides especially in flower production. The present study investigated time-to-pregnancy in the AGRICAN cohort. Methods: Analyses were performed on 616 women reporting a pregnancy (2005 to 2017), and data on agricultural activities performed before the last pregnancy was retrospectively collected. Fecundability odds ratios (fOR) were estimated using a discrete time analogue of Cox proportional hazard model adjusted on maternal and paternal age, body mass index (BMI), and alcohol consumption. Results: A decrease in fecundability was non-significantly associated with farm work (adjusted fOR = 0.86; 95% confidence interval [CI]: 0.71 to 1.05). Decreases were also observed for nightwork (afOR = 0.75; 95% CI: 0.49 to 1.15) and exposure to vibrations (afOR = 0.68; 95% CI: 0.43 to 1.09). Conclusion: Women working on a farm before conception appeared to experience a longer TTP. Negative associations were suggested for some agricultural activities and working conditions. Abstract : Supplemental Digital Content is available in the text